Basic Nutritional Guidelines for Equine Management - Edward L. Johnson; Kylee J. Duberstein (EDIS)
AN235, a 4-page fact sheet by Edward L. Johnson and Kylee J. Duberstein, lists 25 key points to keep in mind when determining how to meet one’s horse’s nutritional requirements. Published by the UF Department of Animal Science, March 2010.